Malaysia's technology sector on its respond to macroeconomic variables / Nur Khalilah Hasnan - Hasnan, Nur Khalilah (Faculty of Business Management, 2018)
Malaysia's economy has taken adverse turns in the recent times and it has become a concern on how to make sure economic growth of the country remains stable and thrive in the future. The problem is to find which macroeconomic variable that affects the Malaysian economy growth. It is in dire need for improvements for the Malaysian economy as to achieve its goals of being a developed country in the future. Recently, the technology sector has been performing well in the stock market which is due to the increase consumption of technology by the nation. Since technology sector has been increasingly contributing to the economy, it indicates the importance of technology to the nation therefore it is believed the technology sector plays an important role in boosting the economy. The objective of this study is to investigate the relationship between macroeconomic variables and the Malaysian technology sector. The data sample for this research includes quarterly data from 2001 to 201 7 for independent variables such as gross domestic product, consumer price index, real effective exchange rate, money supply and the dependent variable that is Malaysian technology sector index. The study found that all the macroeconomic variables are significant to technology sector except for gross domestic product. This researcher hopes policy makers, market participants and future researchers are able to find useful information within this research.